No cookies? - Albee, Sarah (U.S.A : Random House, 2001)
Cookie Monster's visitng nephews prefers to eat a healthy meal before enjoying a plate of freshly baked cookies.
TR/PS
Keywords: Cookies -- Fiction; Food habits -- Fiction; Nutrition -- Fiction; Monsters -- Fiction; Puppets -- Fiction